Primary hyperhidrosis: From a genetics point of view - Asia Parveen; Sidra Abbas; Nasir Mehmood; Mahtab Ahmed Mukhtar Patafi; Usman Wajid; Muhammad Luqman; Shafia Arshad (Journal of Family Medicine and Primary Care)
Primary hyperhidrosis is a disorder of profuse sweating which negatively influences a patient's quality of life and is caused because of over-activation of the sympathetic nervous system. It was believed that hyperhidrosis is a condition limited to only anxious individuals; however, this hypothesis is discredited now. It has been found that people with a positive family history of primary hyperhidrosis are likely to suffer from this condition, suggesting a strong genetic basis. Genetic analysis has revealed a dominant autosomal pattern of inheritance with a variable degree of penetrance and is a sex-independent trait. It is a heterogeneous condition both genetically and clinically as different studies revealed variable genetics and clinical factors. There are no proper criteria for diagnosis as it is not treated as disease by most affected persons. Various studies revealed opposing results in localizing disease gene loci, so further genetic research is needed to pinpoint genes responsible for causing this debilitating condition. Gene expression profiling of human anxiety-causing genes in hyperhidrotic sufferers will also help to devise new treatment modalities. This review highlights the current genetic studies on hyperhidrosis, which may prove to be helpful in understanding the molecular mechanism governing hyperhidrosis.